Bounds on Erdos - Faber - Lovász conjecture - the uniform and regular cases - Hegde, Suresh M.; Dara, Suresh (Electronic Journal of Graph Theory and Applications (EJGTA), 2025)
We consider the Erds - Faber - Lovász (EFL) conjecture for hypergraphs. This paper gives an upper bound for the chromatic number of r regular linear hypergraphs H of size n. If r ≥ 4, χ(H)≤1.181n and if r = 3, χ(H)≤1.281n.